Morphological transformations of the Old Town in Wrocław - Szmytkie, Robert; Pajączek, Kinga (Quaestiones Geographicae, 2023)
The main goal of the article is to present the morphological changes that occurred in the Old Town of Wrocław in the post-war period. Morphological transformation is a natural process that shapes the external and the internal structure of a city. The damage inflicted during World War II interrupted the natural development of the burgage cycle and deeply altered the landscape of the city. Through the analysis of building coverage within street blocks, a classification of street blocks was obtained. On this basis, eight areas that underwent analogous phases of the burgage cycle in particular blocks were distinguished; this made it possible to identify the processes that can affect changes in morphology. The main analysis of the study was conducted using cartographic materials from 1934 to 2019 (through Conzenian methods), which visualised the distribution of buildings within street blocks.